Meningkatkan Keberlanjutan UMKM Melalui Program Pendampingan Keuangan Improving Msme Sustainability Through Financial Assistance Program - Randi Tangdialla; Ade Lisa Matasik (BADAN PENERBIT STIEPARI PRESS, 2021)
Financial assistance programs have a crucial role in improving the sustainability of Micro, Small and Medium Enterprises (MSMEs). The sustainability of MSMEs often depends on their ability to manage finances well. This research aims to explore the benefits and effectiveness of financial assistance programs in the context of MSMEs. The PKM method involves surveys, interviews and data analysis from MSMEs that have participated in the financial assistance program. The main focus of the research is to evaluate the impact of the program on increasing financial understanding, operational efficiency, access to financial resources, and business growth of MSMEs. Financial assistance programs are an effective strategy in improving the sustainability of MSMEs. Recommendations are presented to expand the reach of this program, improve the quality of assistance, and strengthen cooperation between the government, financial institutions and the private sector in supporting MSMEs. Through joint efforts, it is hoped that MSMEs can continue to develop and contribute significantly to economic growth and reducing social inequality